1985
DOI: 10.1007/bf02007698
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine-induced removal of endoplasmic membranes from prolactinoma cells

Abstract: Adenomatous prolactin cells lose 39% of their cytoplasm volume within 7 days after the beginning of bromocriptine treatment. A simultaneous reduction of the rough-surfaced endoplasmic reticulum and the Golgi apparatus occurs. Their membranes are removed by rapid transport along the secretory pathway to the cell surface and to lysosomal destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…In a detailed study, Landolt et al [14] forwarded evidence in support of the former hypothesis. However, the in crease in lysosomal volume density, demonstrated in all but 1 of our cases, suggests that autophagy may play a role in the observed cellular involution.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In a detailed study, Landolt et al [14] forwarded evidence in support of the former hypothesis. However, the in crease in lysosomal volume density, demonstrated in all but 1 of our cases, suggests that autophagy may play a role in the observed cellular involution.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, light microscopic morphome try demonstrates that the overall reduction in cell size is largely attributable to reduced cytoplasmic volume. Sim ilar findings have been obtained in vivo [5][6][7][8][9], leading to the assumption that cytoplasmic depletion is probably a consequence of a reduction in the size of ER and Golgi apparatus [6,14], The present study reveals that ER and Golgi apparatus are the only organelles with consistently reduced cytoplasmic volume densities after treatment. Since dopaminergic agonists, such as bromocriptine, in hibit the synthesis as well as the release of prolactin in rat prolactin cell adenomas [15,16], it is reasonable to assume that similar effects are exerted on human prolac tin cell adenomas.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A further ef fect of bromocriptine was the virtual elimination of cells with electron-dense cytoplasm and greatly dilated ER ('dark' cells) which were a prominent feature during es trogen withdrawal. Bromocriptine-induced loss of ER has been described in prolactin cells [26,27], but the re duction in numbers of 'dark' cells after 2 h exposure to bromocriptine is difficult to explain. The role of these cells is unknown [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that tumor regression induced by bromocriptine therapy is at least partially due to a reduction in cell size of prolactinoma cells [46, 47, 48]. The reduction in cell size by bromocriptine may be attributable to a rapid involution of rough endoplasmic reticulum and Golgi apparatus, as demonstrated by ultrastructural studies [46, 47, 49]. It is tempting to speculate that the dopaminergic action on cell shape and actin organization, as shown in serum-free culture in the present study, is responsible for the reduction in cell size of bromocriptine-treated human prolactinoma cells although it is not yet investigated by other cultures with serum-containing medium whether the dopaminergic action on cell shape can be reproduced universally in vitro.…”
Section: Discussionmentioning
confidence: 99%